Alternative Treatment Modalities for Immature Intruded Permanent Incisors: Report of 2 Cases - Gondim, Juliana Oliveira [UNESP]; Diniz, Michele Baffi [UNESP]; Braga de Abreu-e-Lima, Fabio Cesar [UNESP]; Pansani, Cyneu Aguiar [UNESP]; Siebra Moreira Neto, Jose Jeova (Amer Acad Pediatric Dentistry, 2009)
Intrusion of permanent teeth is one of the most severe types of traumatic injuries. Different treatment strategies have been proposed, and the best approach for each case depends on the stage of root development, severity of the intrusive luxation, presence of alveolar fracture and number of intruded teeth. The purpose of this paper is to describe the treatment management of 2 cases of severely intruded immature permanent maxillary central incisors in 71/2- and 8-year-old children. In case 1, the traumatized tooth was treated by surgical repositioning, while in case 2 watchful waiting for spontaneous re-eruption was the treatment of choice. Treatment strategies were successful in both cases, as demonstrated by the continuation of root development, maintenance of pulp vitality, and absence of signs of per/apical pathosis during the follow-up period. Regardless of the treatment strategy, traumatically intruded teeth should undergo periodical clinical and radiographic surveillance on a long-term basis to allow early detection of possible complications. (Pediotr Dent 2009;31:340-5) Received March 11, 2008 vertical bar Last Revision June 25, 2008 vertical bar Revision Accepted July 16, 2008
Keywords: PERMANENT DENTITION; INTRUSIVE LUXATION; SELF-ERUPTION; SURGICAL REPOSITIONING